High Risk Human Papilloma Virus (HPV) Oropharyngeal Squamous Cell Carcinoma in a Private Tertiary Care Setting in the Philippines: Prevalence, Clinical Characteristics and Testing - Ann Margaret Chang; Marissa Krizelda Santos; William Lim (Philippine Journal of Otolaryngology Head and Neck Surgery, 2023)
ABSTRACT